(untitled) (Journal of Parents and Teachers, 2014)
According to experts, the study of learning strategies is today one of the major focuses of attention for researchers and, in general, to all those who have something to do with the educational intervention. Just take a look to scientific journals, international conferences, specialized publications or college curricula for understanding the development achieved in the last two decades. This article summarizes the nature of the learning strategies by clarifying some constructs that, in general, seem to be quite confusing. Specifically, it is important to distinguish between processes, strategies and techniques. Dealt also with the functions fulfilled in relation to the learning strategies and obviously not leave behind the diagnosis as a fundamental part of the improvement of the processes of knowledge acquisition.